ACG Clinical Guideline: Liver Disease and Pregnancy. (February 2016) - Tran, Tram T; Ahn, Joseph; Reau, Nancy S
Abstract : N/A: Consultation for liver disease in pregnant women is a common and oftentimes vexing clinical consultation for the gastroenterologist. The challenge lies in the need to consider the safety of both the expectant mother and the unborn fetus in the clinical management decisions. This practice guideline provides an evidence‐based approach to common diagnostic and treatment challenges of liver disease in pregnant women.